Martin Heidegger in bistvo tragedije - Gudović, Milosav (Primerjalna književnost, 2013)
This article discusses one of the most representative parts of Heideggers philosophy of literature. In the first section, the author presents the difference between ideas of the fundamental ontologist and Aristotles model of interpretation. In the center of this, a hermeneutical analysis treats the problem of myth perceived as the soul of tragedy and the arrangement of events. Hermeneutical penetration into the truth of the tragic requires an overcoming of the aesthetic oblivion or, in other words, a declination of the mythical frame of life; it also requires a return to the origin of the tragedy as an artistic and religious work. Instead of the sensible purification of individual existence through the experience of fear and pity, in this theoretical milieu the emphasis is more on the primary glade (Lichtung) of Being and the singular arrangement of Event (Ereignis), which seize (er-eignet, er-greift) and comprise the work, the artist, and the recipient. The second aspect of Heideggers hermeneutics of drama is the tragedy of the soula declinatory movement of the tragic man as the most terrible and most powerful being (Seiende) against Being (Sein).
Keywords: Heidegger, Martin, 1989-1976; tragedija; Aristoteles, 384-322 pr.n.š.; filozofija literature; hermenevtika; ontologija; ontology; teorija tragedije; mit; mythology; duša; literarne študije